Context-based variations in EFL teachers' reflection: the case of public schools versus private institutes in Iran. Issue 2 (4th March 2017) - Moradkhani, Shahab; Shirazizadeh, Mohsen
Abstract: The aim of the present study was twofold: examining the effect of contextual differences on the degree of English as a foreign language (EFL) teachers' involvement in reflection and exploring context-related factors that may help/hinder the reflection process. A mixed-methods quantitative-qualitative procedure was adopted. Eighty-five Iranian EFL teachers (41 teaching in public schools and 44 working in private language institutes) completed the English-language teaching reflection inventory developed by Akbari, Behzadpour, and Dadvand (2010 ), with 10 of the participants attending a follow-up interview too. The results of multiple sets of independent samples t -tests showed that teachers in the private sector reported significantly more active involvement in lower levels of reflection (i.e. practical, cognitive, and affective reflection), while no measurable difference was detected between the two groups in terms of higher levels of reflection (i.e. metacognitive and critical reflection). Analysis of the interview data further revealed that teachers' involvement in reflection was influenced by five main context-specific factors namely, knowledge of reflection, institutional demands, teachers' attitude toward teaching, availability of resources, and collegial support. The implications of the findings for educational policymakers and teacher educators were discussed and suggestions were provided for future research.